(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
In this review article describes the chemical characteristics of endocrine disruptors that can contaminate food products used in cattle, likewise its environmental availability and the effects they generate in the homeostasis of this species of zoothecnical interest, with special emphasis on alterations that compromise the reproductive system of male and female bovine, besides the public health consequences generated by the supply of products and byproducts of bovine origin with residues or traces of endocrine disruptors. The ecotoxicology plays an important role in explaining the effects post interaction between xenobiotics and the organisms in an ecosystem; the sources of endocrine disruptors can be found on persistent organic pollutants such as phytoestrogens and these can be present on the inputs used to balance the diets of animals in generating production neuroendocrine changes with economic impact by reducing the reproduction parameters herd.